2012
DOI: 10.3390/molecules171214058
|View full text |Cite
|
Sign up to set email alerts
|

Norcembranoidal Diterpenes from a Formosan Soft Coral Sinularia sp.

Abstract: Two norcembranoidal diterpenes, 5-episinuleptolide acetate (1) and scabrolide D (2), were isolated from a Formosan octocoral identified as Sinularia sp. The structures of norcembranoids 1 and 2 were established by spectroscopic methods and by comparison of the spectral data with those of known analogues and 1 was proven to be a new natural product. Norcembranoid 1 was found to exhibit cytotoxicity toward a panel of tumor cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…850 has revealed that intramuscular injection leads to attenuation of inammation in a monosodium urate model of human gouty arthritis, and that the NP also suppressed neutrophil inltration and expression of related pro-inammatory cytokines. 851 While the mechanisms of cytotoxicity of the cembranoid 5-episinuleptolide acetate 852 appear to include inhibition of levels of Hsp90 and induction of apoptosis, 853 11-episinulariolide acetate 854 targets EGFmediated cytoplasmic calcium levels and inhibits COX-2 and IL-8 expression. 855 Of a range of exo-methylene lactonecontaining cembranoids tested for immunomodulatory effects, lobocrassin B (Lobophytum crassum) 856 was the most effective at blocking TNF-a production and attenuating LPSstimulated dendritic cell maturation and endocytosis.…”
Section: Sesquiterpenes Capillosananementioning
confidence: 99%
“…850 has revealed that intramuscular injection leads to attenuation of inammation in a monosodium urate model of human gouty arthritis, and that the NP also suppressed neutrophil inltration and expression of related pro-inammatory cytokines. 851 While the mechanisms of cytotoxicity of the cembranoid 5-episinuleptolide acetate 852 appear to include inhibition of levels of Hsp90 and induction of apoptosis, 853 11-episinulariolide acetate 854 targets EGFmediated cytoplasmic calcium levels and inhibits COX-2 and IL-8 expression. 855 Of a range of exo-methylene lactonecontaining cembranoids tested for immunomodulatory effects, lobocrassin B (Lobophytum crassum) 856 was the most effective at blocking TNF-a production and attenuating LPSstimulated dendritic cell maturation and endocytosis.…”
Section: Sesquiterpenes Capillosananementioning
confidence: 99%
“…(Taitung County, Taiwan). 760 A collection of Sinularia sp. (Dongluo Is., Hainan, South China Sea) afforded sinuexibilins A-E 962-966, with the authors speculating about the potential artefactual nature of amethoxyfuranocembranoid 966.…”
Section: Cnidariansmentioning
confidence: 99%
“…The straightforward one‐pot conversion of 5‐episinuleptolide into ineleganolide and sinulochmodin C in the presence of LiHMDS seems quite remarkable and provided convincing support for the biosynthesis proposals we made earlier to these novel structures. Interestingly, several months after this work was published, Yen et al isolated 5‐episinuleptolide acetate 119 from a soft coral Sinularia sp collected off the coast of Taiwan.…”
Section: Ineleganolide and Related Norcembranoidsmentioning
confidence: 99%